The Effect of Carbon Emission Disclosure and Green Innovation To Firm Value: Role of Institutional Ownership - Jimmy; Herlin Tundjung Setijaningsih (JURNAL ECONOMINA, 2026)
This study examines the empirical effect of carbon emission disclosure and green innovation on firm value, while examining the moderating role of institutional ownership. Utilizing a quantitative approach, secondary data were obtained from annual and sustainability reports of 172 heavy pollution industry companies listed on the Indonesian Stock Exchange (IDX) during the period 2021–2024, yielding a balance panel of 688 observations analyzed using the random effects model. The empirical results reveal that carbon emission disclosure has significant positive effect on firm value which shows that transparency of carbon emission serves as a credible signal to secure market legitimacy and mitigate information asymmetry. Conversely, green innovation insignificantly affects firm value which shows that developing capital market including Indonesia view eco-friendly research and technology investment as short-term operational cash drains rather than long-term valuable assets. Furthermore, institutional ownership significantly weakens the carbon emission disclosure's positive impact to firm value due to transient investors’ anxieties regarding carbon taxes and regulatory compliance costs, while failing to moderate green innovation's positive effect to firm value due to a passive monitoring posture regarding eco-friendly investments. This research contributes to the literature on sustainability accounting by integrating signal and stakeholder theories within emerging markets. Practically, it provides management with strategic insights to balance environmental compliance and cost efficiency, while advising institutional investors to adopt long-term Environmental, Social and Governance (ESG) integration.